De Sodomitas a Príncipes Mayas: uma análise queer das teopolíticas do Vale do Amanhecer - Calou, Antonio Leonardo Figueiredo (2018)
The Queer movement was born in the final decade of 1970, initially in the United States, and spread to other western countries as a political action that perceived and claimed the forms of heterosexual normality, in the macro and micropolitical contexts of homosexual life, claiming to be disobedient to the patterns which engendered the gay/ lesbian homosexual movement of that period. Their strategies of counterintuitive actions were aimed at affirming, claiming and visibility of bodies considered as strangers and abject to hegemonic standards. Influenced by the audacious works of Michel Foucault and Jacques Derrida, by the currents of poststructuralism and cultural studies, the movement begins to take the scientific and political spaces as a theory, it advances resulting in other analytical also deconstructivist forms to the relations of power that exclude subjects and subalternize their lives. Through the understanding of the epistemological course that traces Queer thought, I sought to establish a post-secular and queer form of analysis to the religions, visualizing through the readings from Foucault, Derrida and Judith Butler, that the theologies of the other manifestations of beliefs make up political discourses that promote ways of regulating bodies, creating unequal power relations between them. I have called this type of teopolistic regulatory strategy, theologies that inform patterns of behavior and assert individuals to follow them. The Valley of the Dawn is a Christian spiritualist doctrine composed of an immense religious hybridity, which causes it to have an articulate conduit-producing discourse for its adherents. Dating back to 1960, the founding father of the clairvoyant Neiva Chaves Zelaya, but known with Aunt Neiva, she is the main agent of theological productions. Starting from this spiritualist context, the objective of this dissertation is to make a queer analysis of the teopolitics of the Valley of Dawn about questions of gender and sexuality. This analysis takes into account the discourses of its main agents, by through the letters, videos and books. The dialogue about religion has the intention of reflecting on how its theologies can lead to an arduous form from normalization of the subjects, especially with regard to the dissident lives of the norms to gender and sex.